Artifical intelligence and international arbitration law: revolution or evolution - Łągiewska, Magdalena (Routledge research in international commercial law, 2026)
The book asks whether the use of Artificial Intelligence (AI) and Generative AI (GenAI) in international arbitration represents a revolution or an evolution of the international dispute resolution landscape. Critically engaging with the transformative impact of the Fourth Industrial Revolution (4IR), this book focuses on the integration of AI and GenAI into international commercial arbitration. Set against the backdrop of rapid technological advancement, it explores how arbitral tribunals and stakeholders are cautiously yet progressively adopting these innovations in a manner that respects and preserves the foundational principles of arbitration. Through an interdisciplinary and practice-oriented approach, the book examines the evolving role of AI in arbitration. It analyzes how AI is perceived and applied by parties, arbitral institutions, and arbitrators, as well as assesses the legal frameworks in place to govern it. Offering a balanced analysis of both the opportunities and legal and ethical dilemmas posed by emerging technologies, the book asks if a duty of disclosure is relevant in relation to AI use, and what challenges this might entail. It also covers the status of AI-generated arbitral awards under international law, as well as copyright law. This book will be of interest to researchers in the field of international arbitration and commercial law
Keywords: Arbitrage; Artificial Intelligence; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Intelligence artificielle; International commercial arbitration; UNCITRAL Model Law on International Commercial Arbitration (1985)

Libérer le potentiel commercial de l'Afrique : Stimuler les marchés régionaux et réduire les risques - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Publications des Nations Unies, 2025)

L'Exécution, condition du procès juste et équitable : actes du séminaire des 15 et 16 mai 2023 - République du Sénégal (Médiateur de la République, 2025)

A path to paperless trade: analysing the legal gaps and economic benefit of adopting or maintaining a legal framework that takes into account the UNCITRAL Model Law on Electronic Transferable Records (MLETR) - Committee on Trade and Investment (CTI) (Asia-Pacific Economic Cooperation, 2025)
Keywords: Asia and the Pacific; DIGITAL TECHNOLOGY; ELECTRONIC COMMERCE; UN Convention on the Use of Electronic Communications in International Contracts (2005); UNCITRAL Model Law on Electronic Commerce (1996); UNCITRAL Model Law on Electronic Transferable Records (2017)

Les grands arrêts de la Cour suprême du Bénin : Chambre judiciaire. Tome 1 - Cour suprême (Bibliothèque de jurisprudence, 2025)
Fidèle à sa vocation de juridiction suprême, la plus vieille de la République, la Cour suprême se veut résolument gardienne du raisonnement juridique au Bénin. Parce qu'elle entend assumer pleinement cette vocation, elle se par conséquent ouverte dans sa mission fondamentale d'interprétation uniforme des lois de la République sur tout le territoire national et d'uniformisation de la jurisprudence.

Les grands arrêts de la Cour Suprême du Bénin : Chambre administrative. Tome 1 - Cour suprême; ASCAP Bénin (Bibliothèque de jurisprudence, 2025)
Fidèle à sa vocation de juridiction suprême, la plus vieille de la République, la Cour suprême se veut résolument gardienne du raisonnement juridique au Bénin. Parce qu'elle entend assumer pleinement cette vocation, elle se par conséquent ouverte dans sa mission fondamentale d'interprétation uniforme des lois de la République sur tout le territoire national et d'uniformisation de la jurisprudence.

Code civil - Institut français d'information juridique (Droit.org, 2025)

Code de commerce - Institut français d'information juridique (Droit.org, 2025)

Code de la consommation - Institut français d'information juridique (Droit.org, 2025)

Code de la propriété intellectuelle - Institut français d'information juridique (Droit.org, 2025)

Code de la sécurité sociale - Institut français d'information juridique (Droit.org, 2025)

Code de procédure civile - Institut français d'information juridique (Droit.org, 2025)

Code de procédure pénale - Institut français d'information juridique (Droit.org, 2025)

Code des assurances - Institut français d'information juridique (Droit.org, 2025)

Code des douanes - Institut français d'information juridique (Droit.org, 2025)

Code des juridictions financières - Institut français d'information juridique (Droit.org, 2025)

Code des ports maritimes - Institut français d'information juridique (Droit.org, 2025)

Code des procédures civiles d'exécution - Institut français d'information juridique (Droit.org, 2025)

Code des transports - Institut français d'information juridique (Droit.org, 2025)

Code du travail - Institut français d'information juridique (Droit.org, 2025)

Code minier (nouveau) - Institut français d'information juridique (Droit.org, 2025)

Code monétaire et financier - Institut français d'information juridique (Droit.org, 2025)

Code pénal - Institut français d'information juridique (Droit.org, 2025)

Livre des procédures fiscales - Institut français d'information juridique (Droit.org, 2025)

Transforming arbitration: exploring the impact of AI, blockchain, metaverse and Web3 - Piers, Maud; McCarthy, Sean (Radboud University Press, 2025)
In an era where technology is rapidly transforming the legal landscape, Transforming Arbitration explores how innovations like AI, blockchain, the Metaverse, and Web3 are reshaping arbitration as a key form of dispute resolution. The book features insights from leading academics, practitioners, and policymakers, offering a comprehensive look at how these advancements are influencing our conceptual, substantive and procedural understandings of many parts of this field. Each chapter examines the challenges and opportunities presented by these technologies, raising important questions about the compatibility of traditional arbitration processes with digital innovations. As the legal field adapts to developments like cryptocurrencies, NFTs, and 'virtual' disputes, this book provides valuable guidance on the future implications for arbitration. By questioning established norms and advocating for fresh approaches, Transforming Arbitration is a vital resource for legal professionals and scholars committed to evolving with the times. Combining theoretical exploration with practical recommendations, this collaborative volume equips the legal community with the tools to navigate the complexities of our digital age with confidence and foresight.
Keywords: AI; Arbitrage; Arbitragem; Arbitration; Artificial Intelligence; Blockchain; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Electronic Commerce; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Římskoprávní kořeny nabytí vlastnického práva přírůstkem v návrhu tereziánské kodifikace soukromého práva a v navazujících revizních osnovách - Šmídová Malárová, Lenka (Publications of the Masaryk University, theoretical series, editions Scientia, 2025)
Monografie představuje výsledky právněhistorické a romanistické analýzy právní úpravy nabývání vlastnického práva přírůstkem (akcesí) v návrhu tereziánské kodifikace soukromého práva z roku 1766 a v navazujících osnovách Hortenově (1776), Martiniho (1796) i finální Zeillerovy, na jejímž základě byl v roce 1811 vydán Všeobecný zákoník občanský (ABGB).
Keywords: Codification du droit; Droit des biens; Droit romain; E-knihy; Elektronické knihy; Knihy; Property law; Propriété; Právní dějiny; Soukromé právo; Vlastnické právo; Čítárna; římské právo

Unlocking Africa's trade potential: Boosting regional markets and reducing risks - United Nations Conference on Trade and Development (United Nations Publications, 2025)

Ghana: Business perspectives - Invisible barriers to trade - International Trade Centre (ITC) (International Trade Centre (ITC), 2024)
This report examines the experiences of Ghanaian exporters and importers with trade regulations and related procedural obstacles – highlighting their concerns and the challenges they face. A survey of 960 traders on non-tariff measures found that almost half of exporters in Ghana encounter obstacles. This finding underscores the importance of the solutions proposed in the country’s National Export Development Strategy. The report finds that tackling foreign and domestic trade obstacles such as conformity assessment requirements, export inspections and customs clearance procedures could help Ghana boost its annual exports by up to $4.3 billion by 2025.

Plataformas de cuidados a mayores - Egea, Mercedes Navarro (Comares, 2024)
La esperanza de vida en nuestro país es una de las más altas del mundo. Se estima que en treinta años la tasa de dependencia de personas mayores con necesidades de cuidados en la UE alcanzará el sesenta por ciento.Este estudio aborda las cuestiones jurídico-tributarias que plantean las "plataformas digitales de cuidados" que operan en el ámbito nacional y que tienen por destinatarios a los mayores dependientes.Estas fórmulas empresariales, además del potencial que tienen para la generación de empleo y la innovación, contribuyen a mejorar la calidad del envejecimiento, pues la oferta de servicios (cuidados de larga duración, por períodos cortos o por horas) se adapta con mayor flexibilidad a las necesidades individuales de los mayores, preservando su independencia y autonomía en todo el ciclo de la vejez. Unos cuidados que han de ser de calidad, asequibles y accesibles.Interesa, por tanto, adentrarse en los aspectos más significativos de lo que podría ser una fiscalidad de plataformas, focalizada en aquellas que actúan como intermediarias conectando a vendedores o prestadores de servicios con usuarios, y que comprende medidas concretas en el IS y el IVA, así como nuevas obligaciones de suministro de información (DAC 7). En esta categoría de plataformas se reconocen la mayoría de las que operan en el ámbito de los cuidados. Y, puesto que se trata de un sector empresarial en crecimiento, presenta especial interés conocer en qué medida se pueden aprovechar las medidas fiscales introducidas para el fomento de las empresas emergentes (startups), así como para la atracción de inversión privada y la captación de talento extranjero.
Keywords: cuidadados; jurídico; mayores; plataformas; tributario

The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On - Heyns, Christof; Viljoen, Frans Jacobus; Murray, Rachel (Brill, 2024)
This collection of chapters tracks and explains the impact of the nine core United Nations human rights treaties in 20 selected countries, four from each of the five UN regions. Researchers based in each of these countries were responsible for the chapters, in which they assess the influence of the treaties and treaty body recommendations on legislation, policies, court decisions and practices. By covering the 20 years between July 1999 and June 2019, this book updates a study done 20 years ago.
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives

Loi type de la CNUDCI sur l'utilisation et la reconnaissance internationale de la gestion de l'identité et des services de confiance - United Nations Commission on International Trade Law (United Nations, 2024)

Uniform Law: Legal Responses to Globalisation - Basedow, Jürgen; Max-Planck-Institut für Ausländisches und Internationales Privatrecht (Hamburg, Germany) (Materialien zum ausländischen und internationalen Privatrecht / Max-Planckt-Institut für Ausländisches und Internationales Privatrecht, 2024)
International conference proceedings
Keywords: COMMERCIAL LAW; Economic Analysis; PRIVATE INTERNATIONAL LAW; Uniform law

Climate Litigation and Justice in Africa - Bouwer, Kim; Etemire, Uzuazo; Field, Tracy-Lynn; Jegede, Ademola Oluborode (Bristol Studies in Law and Social Justice, 2024)
This volume brings together an international team of contributors to provide a much-needed examination of climate litigation in Africa. The book outlines how climate litigation in Africa is distinct as well as pinpointing where it connects with the global conversation. Chapters engage with crucial themes such as human rights approaches to climate governance, corporate liability and the role of gender in climate litigation.
Keywords: Africa; Climate adjudication; Climate governance; Climate justice; Climate litigation

Arbitration rules: In force as from 15 January 2024 - Cairo Regional Centre for International Commercial Arbitration (CRCICA, 2024)

Règlement d'arbitrage : En vigueur à compter du 15 janvier 2024 - Centre régional du Caire pour l’arbitrage commercial international (CRCICA, 2024)

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 1, Daňové právo v proměnách času - Czudek, Damian (Acta Universitatis Brunensis Iuridica Editio Scientia, 2024)
Sborník příspěvků zabývajících se aplikací a interpretací daňového práva, tvorby daňového práva ve smyslu jeho stability a předvídatelnosti, jak z pohledu daňových subjektů (zejména podnikatelů, ale i fyzických osob nepodnikatelů, ale také státu a jemu podřízených organizací (z pohledu předvídatelnosti příjmů do veřejných rozpočtů a stability veřejných financí).
Keywords: Droit fiscal; E-knihy; Elektronické knihy; Fiscalité; Knihy; Tax law; Čítárna

Rechtsformneuschöpfungen im in- und ausländischen Gesellschaftsrecht - Fleischer, Holger (Knowledge Unlatched (KU), 2024)
Gesellschaftsformen bilden die Essenz des Gesellschaftsrechts. Der vorliegende Band untersucht, welche Bereicherungen das Rechtsformentableau in jüngerer Zeit erfahren hat. Als Untersuchungsgegenstand dienen ihm rund 20 ausgewählte Rechtsformneuschöpfungen aus dem In- und Ausland, deren Entstehen und Entwicklung im Einzelnen aufbereitet werden. Wichtige Leitfragen lauten: Wann und warum haben Reformgesetzgeber neue Gesellschaftsformen eingeführt? Von wem stammte die Anregung zu ihrer Einführung? In welcher Hinsicht unterscheiden sie sich von den traditionellen gesellschaftsrechtlichen Gussformen? Wie haben sie sich seither im nationalen und internationalen Rechtsformenwettbewerb behauptet? Durch diese akribischen Einzelstudien entsteht ein facettenreiches Bild des Ideenreichtums in- und ausländischer Reformgesetzgeber mitsamt ihren Wegbereitern aus Unternehmenspraxis, Anwaltschaft, Notariat, Rechtspolitik und Rechtswissenschaft.
Keywords: Commercial law; Comparative law; Conflict of laws

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 2, Výzvy současné sociální politiky - Komendová, Jana; Smejkal, Michal; Tomášková, Eva; Janovec, Michal (Acta Universitatis Brunensis Iuridica Editio Scientia, 2024)
Bezprostřední návaznost pracovněprávních vztahů při posuzování nároku na dovolenou Sociální pojištění a dohoda o provedení práce dle konsolidačního balíčku Implementuje česká právní úprava dostatečně požadavky práva evropské unie na institut zkušební doby? Výzvy sociálnej politiky v kontexte dane z nehnuteľností Lege artis v ohrožení? Výpověď bez udání důvodu aneb jak zvýšit flexibilitu českého pracovního trhu Slovenská právna úprava ochrany oznamovateľov protispoločenskej činnosti z pohľadu rovnakého zaobchádzania v zamestnaní Rovné odměňování zaměstnanců ve skupině společností pohledem českého a evropského práva Výpověď bez udání důvodu jako hybatel pracovního trhu? Prioritizácia manželstva v práve sociálneho zabezpečenia Jak oběti domácího násilí propadávají systémem sociálního zabezpečení Sociální fondy: Co přinášejí zaměstnancům vysokých škol? Revize sociálních dávek Nesezdané soužití – přehlížená sociální realita?
Keywords: Agreement on Work Activity; Agreement on Work Performance; Directive; E-knihy; Elektronické knihy; Immediate Continuity; Knihy; Leave; Čítárna

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 5, Dopravní a přepravní právo v mezinárodním a evropském rozměru - Křepelka, Filip; Richterová, Anna (Acta Universitatis Brunensis Iuridica Editio Scientia, 2024)
Problematika kontrolního vážení v České republice Trestání přestupků v dopravě v evropském rozměru Zajištění dostatečné dopravní obslužnosti Elektromobily jako údajné bezpečnostní riziko v parkovacích domech. Má právo nějak reagovat? AI v oblasti silniční dopravy
Keywords: E-knihy; Elektronické knihy; Knihy; Čítárna

État de la situation sur les impacts sociétaux de l'intelligence artificielle et du numérique - 2024 - Langlois, Lyse; Obvia (Observatoire international sur les impacts sociétaux de l'IA et du numérique, 2024)
L'État de la situation sur les impacts sociétaux de l'intelligence artificielle et du numérique fait état des connaissances actuelles sur les impacts sociétaux de l'IA et du numérique, structurées autour des sept axes de recherche de l'Obvia : santé, éducation, travail et emploi, éthique et gouvernance, droit, arts et médias, et transition socio-écologique. Hypertrucages, désinformation, empreinte environnementale, droit d'auteur, évolution des conditions de travail… Le document recense les grandes questions de recherche soulevées par le déploiement progressif de ces nouvelles technologies, auxquelles viennent s'ajouter des cas d'usages et de pistes d'action. Il s'impose ainsi comme un outil complet et indispensable pour accompagner la prise de décision dans tous les secteurs bouleversés par ces changements.

The Rotterdam Rules Convention: United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea 2008 - Laurijssen, Peter (CMI, 2024)
Keywords: MARITIME LAW; UN Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea (2008)

Property in goods and the CISG - Maier-Lohmann, Till (Recht der internationalen Wirtschaft / Abhandlungen zum Recht der internationalen Wirtschaft, 2024)
Keywords: CONTRACTS; INTERNATIONAL SALE OF GOODS; UN Convention on Contracts for the International Sale of Goods (1980)

Derecho penal económico y de la empresa - Mata Barranco, Norberto J. de la; Dopico Gómez-Aller, Jacobo; Lascuraín Sánchez, Juan Antonio; Nieto Martín, Adán (Dykinson, 2024)

Jus Mundi Arbitration Review - Mistelis, Loukas; Fan, Kun (JMAR, 2024)
Articles The Seven Cardinal Sins of Investment Dispute Settlement Investment Arbitration in the New Era: Engine or Obstacle in the Fight Against Climate Change? The UNIDROIT Principles as a Tool for the Internationalisation of Contracts by Arbitral Tribunals AI: The Modern Tribunal Assistant – Impact on Enforceability of Arbitral Awards under the New York Convention Automation & Augmentation: Artificial Intelligence in International Arbitration The IBA Guidelines on Conflicts of Interest in International Arbitration 2024 CIETAC: Overview of Dispute Resolution in the Digital Environment in China Swiss Supreme Court rejects CJEU’s Komstroy ruling Romania’s Supreme Court Decides that Associations and Foundations Based in Romania Can Only Set Up Arbitral Institutions if Authorized by Law Book Review – On Arbitration: V. V. Veeder QC, Selected Writings and Contributions to the Development of Law (Wordsworth & Veeder (eds), OUP 2023) Book Review – Investment Arbitration and Climate Change (Ipp & Magnusson (eds), Kluwer 2024)

Les contrats dans le secteur de l'édition : Guide à l'intention des auteurs et des éditeurs - Organisation mondiale de la Propriété intellectuelle (OMPI, 2024)
Keywords: Contrat d'édition; Droits d'auteur; Editeur; Edition

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců.. Část 8, Regulace, dohled a inovace na finančních trzích a v bankovním sektoru - Schweigl, Johan; Holubářová, Nikol (Acta Universitatis Brunensis Iuridica Editio Scientia, 2024)
- Právní aspekty zavedení Centrální bankovní digitální měny (CBDC) v Evropě: výzvy a; - Novinky ve světě fintech; - Riziko praní špinavých peněz v kryptoprostoru; - Povolenie na poskytovanie služieb kryptoaktív podľa nariadenia MiCA – vybrané regulačné aspekty v podmienkach Slovenskej republiky; - Nekalé obchodní praktiky a nekalosoutěžní jednání v bankovním marketingu; - Finančné inovácie ako determinant súčasnej a anticipovanej regulácie na finančnom trhu v kontexte neoprávneného podnikania; Outsourcing marketingových aktivit v bankovním sektoru; Několik poznámek k dlouhodobému investičnímu produktu.

COFOLA 2024: Sborník příspěvků mladých právníků, doktorandů a právních vědců. Část 3, Aktuální otázky náhrady škody - Schweigl, Johan; Holubářová, Nikol; Janovec, Michal (Acta Universitatis Brunensis Iuridica Editio Scientia, 2024)
Sborník příspěvků z konference. OBSAH - Kdo odpovídá za škodu způsobenou zvířetem? Otázka odpovědnosti a náhrady škody ve vztahu k živočišné říši - Náhrada nemajetkové újmy na zdraví: smíření s Metodikou, návrat k prováděcím předpisům nebo třetí cesta? - Náhrada škody v případech věcí, které jsou předmětem zvláštní obliby - Náhrada škody v případě neprodejnosti výrobků obsahující hhc látky a celkový dopad na podnikání jednotlivců - Právo na zadostiučinění v souvislosti s rozhodováním orgánů družstva - Újma způsobená neprodloužením života závažně nemocné osoby
Keywords: E-knihy; Elektronické knihy; Flipbook; Knihy; Masarykova univerzita; Munipress; Čítárna

The Individual in International Law: History and Theory - Sparks, Tom; Peters, Anne (The History and Theory of International Law, 2024)
Keywords: Humanisation; Individual; Individualisation; International law; Legal history; Legal theory

UNCITRAL Model Clause on Adjudication - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Confidentiality - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Highly Expedited Arbitration - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL Model Clause on Technical Advisers - UNCITRAL (United Nations, 2024)
The UNCITRAL Model Clauses on Specialized Express Dispute Resolution (SPEDR) (2024) (the “Model Clauses”) have been developed and adopted by the United Nations Commission on International Trade Law. The Model Clauses, accompanied by explanatory notes, offer customized solutions designed to be adapted and adjusted to suit the particular circumstances and preferences of the parties, building on the UNCITRAL Expedited Arbitration Rules. Designed as a resource for businesses and practitioners engaging in international dispute resolution, especially when speed and technical expertise are crucial factors, the Model Clauses provide parties with tailored means to settle disputes in an expeditious manner, ensuring the integrity and effectiveness of their dispute resolution processes, while catering for their unique needs. The Four Model Clauses presented are: Model Clause on Highly Expedited Arbitration Model Clause on Adjudication Model Clause on Technical Advisers Model Clause on Confidentiality

UNCITRAL, HCCH, Unidroit Guida giuridica agli strumenti uniformi in materia di contratti commerciali internazionali, con particolare attenzione alle vendite - United Nations; UN Commission on International Trade Law (Giuffre Francis Lefebvre, 2024)
Keywords: Hague Principles on Choice of Law in International Commercial Contracts; International sale of goods; UN Commission on International Trade Law; UN Convention on Contracts for the International Sale of Goods (1980); UNIDROIT Principles of International Commercial Contracts (2016)

Unpacking the African continental free trade area: A glossary - International Trade Centre (ITC) (International Trade Centre (ITC), 2023)
This glossary is the first edition of legal and other terms that micro, small and medium enterprises (MSMEs) will encounter while trading under the African Continental Free Trade Area (AfCFTA). The aim of the glossary is to help users understand legal, commercial and customs terms found in the AfCFTA Agreement as it has been crafted with inputs and guidance from the African private sector, including MSMEs, women and youth entrepreneurs, and business support institutions striving to improve the African business environment.
Keywords: AfCFTA; Glossaire; Lexique; ZLECAf

Justice civile amiable, justice pénale négociée... vers une justice consensuelle ? (Revue Justice Actulaités, 2023)
Keywords: Conciliation; Conciliação (processo civil); Consentement; Justice amiable; Justice négociée; Médiation; Politique de l'amiable; Procédure pénale

The Concise Encyclopedia of Business Ethics - MacDonald, Chris; Marcoux, Alexei (Toronto Metropolitan University, 2023)
The authors’ aim in writing The Concise Encyclopedia of Business Ethics (CEBE) was to provide readers with a useful, concise overview of key issues in business ethics. Our aim is not to be exhaustive, but to provide key definitions, main areas of controversy, and pointers for further reading. It is hoped that it will provide a useful reference guide for students, as well as a starting point for scholars in adjacent fields. Our commitment to sticking to what we consider to be essential topics inevitably means that some readers will find that we have left out what they take to be important topics. For the most part, we stand by our editorial choices. However, as a digital document, it is possible that the CEBE will change and grow slightly over the coming years. Readers are free to provide feedback and suggestions by emailing the authors jointly at editors@bejr.org

Les promesses des technologies au service du commerce: Politiques visant à tirer parti de la numérisation du commerce - Organisation mondiale du commerce (WTO, 2023)
Les promesses des technologies au service du commerce – l'ensemble de technologies grâce auxquelles le commerce mondial peut devenir plus efficace, plus inclusif et plus durable – sont nombreuses, depuis la facilitation des échanges jusqu'aux gains d'efficacité et à la réduction des coûts en passant par l'amélioration de la transparence et de la résilience des chaînes d'approvisionnement. Certes, l'innovation technologique existe, mais le plus grand défi en ce qui concerne l'adoption des technologies au service du commerce à l'échelle mondiale consistera à mettre en place une coordination internationale des politiques. Les accords commerciaux peuvent jouer un rôle primordial. En dépit des efforts actuels en vue d'introduire des dispositions relatives au commerce numérique, il subsiste nombre de possibilités inexploitées et de politiques inexplorées. Cette publication conjointe du Forum économique mondial et de l'OMC examine de quelle façon les accords commerciaux pourraient être mobilisés pour faire progresser l'adoption des technologies numériques et la numérisation du commerce.
Keywords: Accords régionaux de commerce; Commerce électronique; Technologies de l'information

Les chaînes d’approvisionnement mondiales à forte intensité technologique : le potentiel de l’Afrique - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Publications des Nations Unies, 2023)

The Potential of Africa to capture technology-intensive global supply chains - United Nations Conference on Trade and Development (United Nations Publications, 2023)

Corporate Finance, Governance, and Social Responsibility - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers 27 papers published in the Special Issue entitled Corporate Finance, Governance, and Social Responsibility, which examines several topics related to corporate finance, financial modeling, corporate governance, and corporate social responsibility. Corporate finance-related articles (Anton and Afloarei Nucu, 2021; Bae et al., 2023; Kedzior et al., 2020; Lts and Lukason, 2022; Miglo, 2020; Mihail et al., 2021; Mota and Moreira, 2023; Tsolas, 2021; Tudose et al., 2021; and Wen et al., 2021) focus on the drivers of the capital structure and firm performance, the effect of working capital management on profitability, and the link between derivative use and profitability. Regarding financial modeling, stock market volatility was explored during COVID-19 (Gherghina et al., 2021). Corporate governance studies (Aluchna and Kuszewski, 2020; Ararat et al., 2021; Ding and Chea, 2021; Kjrland et al., 2020; Loureno et al., 2021; Lukason and Camacho-Miano, 2020; Maier and Yurtoglu, 2022; Mihail and Dumitrescu, 2021; Mihail et al., 2022; Mihail and Micu, 2021; and Pourmansouri et al., 2022) examine the effect of corporate governance compliance practices, board attributes, or employee stock option plans on bankruptcy risk, performance, firm value, or earnings management. Regarding CSR (Bozos et al., 2022; Rossi et al., 2021; Saeed and Sroufe, 2021; Singh and Hong, 2023; and Tseng and Shih, 2022), the research focuses on how CSR affects financial performance, risk management, or analyst profits estimates.
Keywords: CSR; Corporate Finance; Financial performance

Third Party Funding in International Arbitration: A Critical Appraisal and Pragmatic Proposal - Sweify, Mohamed (Edward Elgar Publishing, 2023)
The author of Third Party Funding in International Arbitration challenges the structural inconsistencies of the current practices of arbitration funding by arguing that third party funding should be a forum of justice, rather than a forum of profit. The author introduces a new methodology with an alternative way of structuring third party funding to solve a set of practical problems generated by the risk of claim control by the funder.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitral justice; Arbitration; Claim control; Dispute outcome; Financement; Funders; Third Party Funding; Tiers

Cadre de convergence réglementaire du transport routier et sa stratégie d’application sous-régionale en Afrique de l’Ouest - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Nations Unies, 2023)

Des mots appelés à la barre : vocabulaire du droit - Le Barreau du Québec et ses avocats (Office québécois de la langue française, 2023)

Le terrorisme au Benin: perceptions, actions et perspectives / Sous la direction de Thierry S. Bidouzo et Expédit B. Ologou ; avec les contributions de Vincent Afouda Agué, Estelle Djanato, Emmanuel Odilon Koukoubou (Friedrich-Ebert-Stiftung Bénin, 2023)
Longtemps considéré comme un havre de paix, le Bénin se retrouve pris au piège de la menace terroriste, subissant des attaques depuis décembre 2021. Les groupes armés venus du Sahel frappent de plus en plus les pays côtiers du golfe de Guinée et provoquent l'exacerbation des dynamiques conflictuelles dans la région. Le fléau du terrorisme et de l'extrémisme violent prend une grande ampleur notamment dans les zones septentrionales du Bénin, où les attaques prennent de plus en plus des formes de violences extrêmes. La vie quotidienne des populations, la quiétude, la cohésion sociale sont alors hypothéquées, car otages des groupes armés terroristes. Comme face à tout péril réel, imminent ou lointain, des interrogations, des perceptions, des résolutions, des attentes ne sauraient manquer dans les pensées des Béninois. La présente étude tente une restitution de ces pensées citoyennes sur la menace terroriste.

Entreprises et droits de l'Homme : Protéger, respecter, réparer - Commission nationale consultative des droits de l'homme (La documentation française, 2023)
Le rapport vise à analyser les développements normatifs et les politiques menées par la France sur la thématique Entreprises et droits de l’Homme depuis l’adoption de son plan national d’action, aux niveaux international (première partie), régional (deuxième partie) et national (troisième partie). La CNCDH formule 145 recommandations, dont 20 prioritaires, afin d’encourager la France à redoubler d’ambition pour le respect et la protection des droits de l’Homme dans le contexte des activités des entreprises. Il s’agit d’améliorer la mise en œuvre des cadres normatifs et mécanismes existants, de soutenir de futurs développements normatifs qui constituent un nivellement par le haut et de lever les obstacles à l’accès aux voies de recours et à la réparation, pour s’assurer qu’en cas de violations des droits de l’Homme commises, directement ou indirectement, par les entreprises, leur responsabilité puisse être engagée.

Redesigning Protection for Consumer Autonomy: The case-study of dark patterns in European private law - Guerra, Giorgia (FrancoAngeli, 2023)
European legal protection of consumer autonomy has been significantly changed in the digital environment, where algorithm-driven systems perform everything. This book focuses on protecting consumer autonomy facing the pervasive and global phenomenon of dark patterns: the expression includes various tactics that manipulate consumers by altering online choice architecture to thwart user preferences for objectionable ends. Overloading, skipping, stirring, hindering, and flicking are examples. Moving from the perspective that the sole traditional information approach is ineffective in protecting autonomy, the adopted methodology considers the multiple concerns revolving around the tight combination of transparent information and fair digital architectural design. Consequently, the comparative study of the new suitable regulatory directions arises across different legal fields, including data protection, consumer, and competition law. The relationship between deceptive designs, the nature of human-digital architecture interaction, and the techno-legal paradigms emphasises which future changes in European private law could integrate legal rules into fair designs to protect digital consumer autonomy effectively. Specific importance will be attributed to the functionality of comparative methodology to include non-legal essential insights (e.g. behavioural, informatic elements) into pragmatic and global regulatory paths and models.
Keywords: Autonomy; Consumer law; Dark Patterns; Data protection law; Design regulation; Digital law; European private law

Effective Conflict Management - International Chamber of Commerce (ICC Publication DRS, 2023)

Transnationale Verträge im nationalen Recht: Theorie und Dogmatik transnationaler Ordnungsstrukturen am Beispiel von Musterverträgen im Finanzbereich - Kindt, Torsten (Mohr Siebeck, 2023)
Weltweit vereinheitlichte Musterverträge bestimmen die Vertragsgestaltung im grenzüberschreitenden Finanzverkehr. Diese Musterverträge werden von privaten Organisationen wie der International Chamber of Commerce (ICC), der Loan Market Association (LMA) und der International Swaps and Derivatives Association (ISDA) geschaffen. Torsten Kindt zeigt, dass auf Grundlage der Muster ein bereichsspezifisches transnationales Vertragsrecht entsteht, das jedoch auf vielfältige Weise mit dem staatlichen Recht verwoben bleibt. Er entwickelt Leitlinien für einen responsiven Umgang mit musterbasierten transnationalen Verträgen im staatlichen Kollisions-, Vertrags- und Internationalen Zivilverfahrensrecht, die auch über den Finanzbereich hinaus zu einem produktiven Zusammenwirken privater und staatlicher Ordnung beitragen können.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Bankruptcy; Civil Law; Dispute resolution; Insolvency; Litigation; MARD; Mediación; Mediation; Mediação; Médiation; Negotiation

The Law Applicable to Security Interests in Intermediated Securities Under OHADA Law - Monsenepwo Mwakwaye, Justin (Knowledge Unlatched (KU), 2023)
In recent decades, the technical handling of custody business in the OHADA region has undergone a lasting change. There has been a shift from a direct to an indirect holding system, in which the interests of an investor in respect of the underlying securities are recorded in the books of an intermediary (such as a bank or a securities firm). Under the law of all states within the OHADA region, the traditional conflict of laws rule for determining the enforceability of a securities pledge that occurs in the indirect holding system is the lex rei sitae (or the lex cartae sitae or the lex situs ) rule. However, the traditional lex rei sitae rule cannot be appropriately applied to a system where the dematerialised securities are held through multiple layers of intermediaries located in different jurisdictions. Yet, until the intermediated system and the collateralisation of intermediated securities in the OHADA region will continue to operate in somewhat legally murky waters, leading to more instability in the financial markets. Therefore, Justin Monsenepwo aims to find an appropriate and consistent approach that reflects the reality of the indirect holding system in the OHADA region. “This publication is essential reading for policy makers, academics, market participants, and legal practitioners in the OHADA region and beyond. I am convinced that its in-depth analysis of OHADA’s substantive and conflict of laws rules will go a long way in filling the gap in this area and encouraging further development in the future.” Christophe Bernasconi, Secretary General of the „Hague Conference on Private International Law“ – HCCH in the foreword
Keywords: Commercial; Commercial law; Comparative; Comparative law; Competencia; Competition law; Conflict of laws; Law; Private international law

Guide de la prévention des difficultés des entrprises - Mouvement des entreprises de France (MEDEF, 2023)

Intellectual Property Law in Africa: Harmonising Administration and Policy - Ncube, Caroline B. (Routledge Research in Intellectual Property, 2023)
Examining the harmonisation of Intellectual Property policy, law and administration in Africa, this book evaluates the effectiveness of efforts to establish continental Intellectual Property institutions and frameworks. It also considers sub-regional initiatives led by the regional economic communities and the regional Intellectual Property organisations, focusing on relevant protocols and agreements that address Intellectual Property as well as the implementing institutions. The book assesses the progress of such initiatives with particular reference to the current socio-economic status of African states. It argues that that harmonisation initiatives need to be crafted in a way that is supportive of the developmental goals of African states and advocates for due consideration of individual states’ unique conditions and aspirations. This book will be of great relevance to scholars and policy makers with an interest in Intellectual Property law and its harmonisation in Africa.
Keywords: Africa; Droit (harmonisation); Intellectual property; Public interest; TRIPs; governance; thema EDItEUR::G Reference

African Principles on the Law Applicable to International Commercial Contracts - Neels, Jan (UJ Press, 2023)
This booklet contains the first draft of the envisaged African Principles on the Law Applicable to International Commercial Contracts. The proposal could be used by national legislators on the continent and African economic integration organisations, particularly the African Union, in, respectively, domestic legislation and regional or supranational laws of a soft or binding nature. The existence of a reliable transnational legal infrastructure in respect of international commercial law, including commercial private international law, is a prerequisite for investor confidence, inclusive economic growth, sustainable development, and the ultimate alleviation of poverty on the African continent. The instrument may contribute to sustainable growth on a long-term basis. The regulation of private international law of contract is essential to the further development of the African Continental Free Trade Area. Jan L Neels is professor of private international law and director of the Research Centre for Private International Law in Emerging Countries at the University of Johannesburg.
Keywords: African principles; International commercial contracts

The International Handbook of Social Enterprise Law: Benefit Corporations and Other Purpose-Driven Companies - Peter, Henry; Vargas Vasserot, Carlos; Alcalde Silva, Jaime (Springer Nature, 2023)
This open-access book brings together international experts who shed new light on the status of social enterprises, benefit corporations and other purpose-driven companies. The respective chapters take a multidisciplinary approach (combining law, philosophy, history, sociology and economics) and provide valuable insights on fostering social entrepreneurship and advancing the common good. In recent years, we have witnessed a significant shift of how business activities are conducted, mainly through the rise of social enterprises. In an effort to target social problems at their roots, social entrepreneurs create organizations that bring transformative social changes by considering, among others, ethical, social, and environmental factors. A variety of social enterprise models are emerging internationally and are proving their vitality and importance. But what does the term “social enterprise” mean? What are its roots? And how does it work in practice within the legal framework of any country? This handbook attempts to answer these questions from a theoretical, historical, and comparative perspective, bringing together 44 contributions written by 71 expert researchers and practitioners in this field. The first part provides an overview of the social enterprise movement, its evolution, and the different forms entities can take to meet global challenges, overcoming the limits of what governments and states can do. The second part focuses on the emergence of benefit corporations and the growing importance of sustainability and societal values, while also analyzing their different legal forms and adaptation to their regulatory environment. In turn, the last part presents the status quo of purpose-driven companies in 36 developed and emerging economies worldwide. This handbook offers food for thought and guidance for everyone interested in this field. It will benefit practitioners and decision-makers involved in social and community organizations, as well as in international development and, more generally speaking, social sciences and economics.
Keywords: B-Corps; BCorp Certification; Benefit Corporations; Business and Management; Business ethics; CSR; Commercial Law; Competencia; Competition law; Corporate Social Responsibility; Finance; Social Business Inititive; Social Enterprises; Social Entrepreneurship

Recueil de textes communautaires sur la libre circulation et le droit d'établissement - Union Economique et Monétaire Ouest Africaine (UEMOA, 2023)

The Idea of Economic Constitution in Europe: Genealogy and Overview - Grégoire, Guillaume; Miny, Xavier (Legal History Library, 2022)
Derrière les controverses qui jalonnent l’histoire de l’idée de Constitution économique émerge la question éminemment politique de la marge de manœuvre laissée aux autorités publiques dans la sphère économique. La notion cristallise ainsi une tension fondamentale : entre démocratie et État de droit, quel doit être modèle d’organisation et d’ordonnancement juridique de l’économie? Des physiocrates aux néolibéraux, de la République de Weimar à l’intégration européenne, des constitutions nationales à la Global Governance, cet ouvrage collectif nous invite dès lors à explorer la généalogie du concept polémique de Constitution économique. Les auteurs ouvrent alors, à travers un dialogue interdisciplinaire constant, une réflexion globale autour des enjeux juridiques et politiques du processus actuel de constitutionnalisation de l’ordre de marché en Europe.
Keywords: Constitutional Law; Economic History; History; International Law; Legal History

Lexique des termes juridiques (AFTI, 2022)

The Singapore Convention on Mediation: a commentary - Alexander, Nadja; Chong, Shouyu; Giorgadze, Vakhtang (Kluwer Law International, 2022)
Article-by-article commentary
Keywords: Dispute Settlement; MARD; Mediación; Mediation; Mediação; Médiation; UN Convention on International Settlement Agreements resulting from Mediation (2018)

L'argumentation juridique - Bontems, Camille; Courtemanche, France; Levesque, Anne (Université d’Ottawa, 2022)
L’expertise du juriste ou de l’avocat ne s’arrête pas à la maîtrise du droit. Il doit non seulement pouvoir déterminer les règles de droit applicables dans une situation donnée, mais aussi savoir les utiliser et les présenter pour convaincre un juge du bien-fondé de la position qu’il défend. Dans cette veine, il est nécessaire de pouvoir argumenter de manière pertinente et convaincante. Il existe de nombreuses manières d’argumenter. Sans chercher à toutes les présenter, nous tenterons ici de vous présenter quelques éléments pour vous aider à construire vos premiers argumentaires juridiques. Ressource éducative libre pour le cours CML 1611 Compétences et habiletés juridiques à l’Université d’Ottawa (Faculté de droit – Common Law).
Keywords: Argumentation juridique; Common law; Raisonnement juridique; Rédaction

Règlements d’Arbitrage en vigueur à compter du 1er janvier 2021 et de Médiation en vigueur à compter du 1er janvier 2014 - Chambre de commerce internationale (ICC Publication DRS, 2022)
Keywords: Arbitrage; Arbitragem; Arbitration; MARD; Mediación; Mediation; Mediação; Médiation; Règlement d'arbitrage; Règlement de médiation

Contract Interpretation in Investment Treaty Arbitration: A Theory of the Incidental Issue - Chernykh, Yuliya (International Litigation in Practice, 2022)
For the first time, a monograph provides a systematic, in-depth account of contract interpretation in investment treaty arbitration and offers a conceptual paradigm that would enhance the quality of the tribunals’ reasoning.; Readership: The monograph is of relevance for legal scholars, practitioners and policymakers in the field of investment treaty arbitration. The book will also be of additional value to postgraduate and doctoral students.
Keywords: Arbitrage; Arbitragem; Arbitration; Contract interpretation; International law; Investment arbitration; Investments

Guide to the writing of law for the Social and Solidarity Economy - Hiez, David (SSE International Forum, 2022)
Keywords: Cooperatives; Social Enterprises; Social and Solidarity Economy

Arbitration Rules In force as from 1 January 2021 and Mediation Rules In force as from 1 January 2014 - International Chamber of Commerce (ICC Publication DRS, 2022)
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration rules; MARD; Mediación; Mediation; Mediation rules; Mediação; Médiation

Los medios jurisdiccionales de solución de las controversias internacionales : avances y nuevos retos - Petrova Georgieva, Virdzhiniya (Doctrina Jurídica, 2022)

Nomenclature Tarif Extérieur Commun : Règles générales pour l’interprétation du Système harmonisé - Union Economique et Monétaire Ouest Africaine (UEMOA, 2022)

Diccionario de Términos de Política Comercial - Goode, Walter (Organización Mundial del Comercio, 2021)
Este diccionario es una guía accesible al vocabulario empleado en las negociaciones comerciales. En él se explican unos 3.000 términos y conceptos en un lenguaje sencillo. Se dedica especial atención al sistema multilateral de comercio, representado por los acuerdos de la Organización Mundial del Comercio (OMC). El diccionario abarca, además, muchas de las actividades, resultados y términos relacionados con el comercio utilizados en otras organizaciones internacionales, tales como la Conferencia de las Naciones Unidas sobre Comercio y Desarrollo (UNCTAD), la Organización Mundial de la Propiedad Intelectual (OMPI), la Organización de las Naciones Unidas para la Alimentación y la Agricultura (FAO), el Foro de Cooperación Económica de Asia y el Pacífico (APEC) y la La Organización para la Cooperación y el Desarrollo Económicos (OCDE). En el pasado decenio se ha prestado considerable atención a la facilitación del comercio y las inversiones, la sostenibilidad y la formación de zonas de libre comercio en todas las partes del mundo. El diccionario dedica un amplio espacio al vocabulario relacionado con esa evolución. Ofrece, por ejemplo, explicaciones claras de los conceptos utilizados en la administración de las normas de origen preferenciales. Más recientemente, la facilitación del comercio ha sido objeto de gran atención. Otras de las esferas abarcadas son los nuevos temas comerciales y las cuestiones relacionadas en particular con las preocupaciones de los países en desarrollo. Durante muchos años, Walter Goode fue funcionario del Ministerio de Relaciones Exteriores y Comercio Internacional de Australia. En el ejercicio de sus funciones, adquirió una amplia experiencia en la formulación de la política comercial internacional y la celebración de negociaciones comerciales bilaterales y multilaterales. En particular, participó en negociaciones y reuniones en el APEC, el GATT, la OMC, la UNCTAD y la OCDE. Ha ocupado puestos relacionados con el comercio en Ginebra, Beijing, Shanghái y Tokio. Impartió numerosos cursos de formación sobre política comercial, en particular bajo los auspicios del APEC. En la actualidad está jubilado. Entre sus publicaciones figuran: Australian Traded Services, Uruguay Round Outcomes: Services y Negotiating Free-Trade Agreements: A Guide.

Legal Guide on Agricultural Land Investment Contracts - UNIDROIT; IFAD (UNIDROIT/IFAD, 2021)

Big Data and Global Trade Law - Burri, Mira (Cambridge University Press, 2021)
This collection explores the relevance of global trade law for data, big data and cross-border data flows. Contributing authors from different disciplines including law, economics and political science analyze developments at the World Trade Organization and in preferential trade venues by asking what future-oriented models for data governance are available and viable in the area of trade law and policy. The collection paints the broad picture of the interaction between digital technologies and trade regulation as well as provides in-depth analyses of critical to the data-driven economy issues, such as privacy and AI, and different countries' perspectives. This title is also available as Open Access on Cambridge Core.
Keywords: AI; Artificial Intelligence; Big data; Blockchains (Databases); Data protection––Law and legislation; Foreign trade regulation; Inteligência artificial; Intelligence Artificielle; Law and legislation; Transborder data flow––Law and legislation.; World Trade Organization

Proceedings of 2021 UNCITRAL Working Group III inter-sessional meeting: the use of mediation in ISDS - Asian Academy of International Law Limited (AAIL) (Asian Academy of International Law Limited, 2021)
Keywords: Dispute settlement; Investment disputes; MARD; Mediación; Mediation; Mediação; Médiation; UN Commission on International Trade Law; UN Convention on International Settlement Agreements resulting from Mediation (2018)

Lexique juridico-judiciaire français-arabe - Benbouza, Mohammed (PASJA, 2021)

L’avenir du travail en Afrique : exploiter le potentiel des technologies numériques pour un monde du travail plus inclusif - Choi, Jieun; Dutz, Mark A.; Usman, Zainab (L'Afrique en développement, 2021)

Vers la mise en place d’une zone d’investissement commune au sein de la Zone de libre-échange continentale africaine : uniformiser les conditions régissant les investissements intra-africains - Commission Économique Pour l'Afrique (Nations Unies, 2021)
Le présent rapport prône l’adoption de mesures de lutte contre la COVID concernant tout particulièrement la politique d’investissement soutenue par l’Accord portant création de la Zone de libre-échange continentale africaine afin de préserver les acquis du marché commun pour les entreprises et les citoyens africains et d’accroître les avantages en découlant. La Zone de libre-échange continentale africaine (ZLECAf) contribuera à générer les ressources financières nécessaires au développement économique de l’Afrique. Elle a pour objet de mettre en place un marché africain intégré où les biens, les personnes, les services et les capitaux circulent librement, complétant les efforts d’intégration régionale au profit des 1,3 milliard d’habitants du continent. Le produit intérieur brut combiné du marché de la ZLECAf est de 2 500 milliards de dollars. Elle a officiellement vu le jour le 21 mars 2018 à Kigali, date à laquelle 44 États membres de l’Union africaine ont signé l’Accord portant création de la Zone de libre-échange continentale africaine. L’Accord est entré en vigueur le 30 mai 2019 après le dépôt de l’instrument de ratification par le 22ème État membre de l’UA. La ZLECAf est entrée dans sa phase opérationnelle en juillet 2019. Les échanges régis par les règles de la ZLECAf ont débuté le 1er janvier 2021.

Corporate Finance - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book comprises 19 papers published in the Special Issue entitled “Corporate Finance”, focused on capital structure (Kedzior et al., 2020; Ntoung et al., 2020; Vintilă et al., 2019), dividend policy (Dragotă and Delcea, 2019; Pinto and Rastogi, 2019) and open-market share repurchase announcements (Ding et al., 2020), risk management (Chen et al., 2020; Nguyen Thanh, 2019; Štefko et al., 2020), financial reporting (Fossung et al., 2020), corporate brand and innovation (Barros et al., 2020; Błach et al., 2020), and corporate governance (Aluchna and Kuszewski, 2020; Dragotă et al.,2020; Gruszczyński, 2020; Kjærland et al., 2020; Koji et al., 2020; Lukason and Camacho-Miñano, 2020; Rashid Khan et al., 2020). It covers a broad range of companies worldwide (Cameroon, China, Estonia, India, Japan, Norway, Poland, Romania, Slovakia, Spain, United States, Vietnam), as well as various industries (heat supply, high-tech, manufacturing).

Dictionnaire des termes de politique commerciale - Goode, Walter (Organisation mondiale du commerce, 2021)

La transparence des industries extractives en Afrique - Krolik, Christophe; Moumouni, Charles (Sociétés africaines en mutation, 2021)
La transparence des industries extractives en Afrique s’inscrit dans un contexte de développement durable. Elle rejoint la question du développement du continent africain qui dépend des revenus générés par l’exploitation de ses abondantes ressources minières, pétrolières et gazières. La notion est souvent perçue comme une obligation de reporting financier et extra-financier. Toutefois, en raison de la pluralité des sources, les enjeux sont bien plus complexes. Une meilleure compréhension et une application adéquate de la transparence concourent à la bonne gouvernance du secteur extractif, qui demeure un défi permanent et urgent pour le continent africain. Pourtant, la transparence dans l’exploitation des ressources naturelles et énergétiques de l’Afrique était jusqu’ici peu documentée. Cet ouvrage comble ce besoin par les contributions d’experts de renommée internationale autour d’une réflexion sur les mesures et moyens les plus idoines à mobiliser. Il combine des approches et des sources variées allant dans le sens du développement durable de l’Afrique. Les résultats offrent un contenu original à l’analyse précise, critique et prospective. Une importance capitale est accordée à la pratique sur le terrain à travers des études de cas illustratifs. Ce livre de référence s’adresse aux universitaires et aux professionnels souhaitant disposer d’une vision concrète de la transparence du secteur extractif en Afrique.

La salida voluntaria del socio profesional en las sociedades de capital - Lorenzo Camacho, María Salomé (Dykynson, 2021)
Ministerio de Economía, Industria y Competitividad en el marco del Plan Estatal de Investigación Científica y Técnica y de Innovación 2013-2016 DER2017-84775-C2-1-P

Le droit des coopératives en Afrique : Réflexions sur l'Acte uniforme de l'OHADA - Tadjudje, Willy (Éditions et presses universitaires de Reims, 2021)
"The aim of this book is to analyse the level of implementation of the Uniform act on cooperatives (Acte uniforme relatif au droit des sociétés coopératives, AUSCOOP) ten years after its enactment. The authors' analysis, conclusions and recommendations lead to two main ideas: on the one hand, the need to correct the weaknesses and inconsistencies of the Act, and on the other hand, the lack of coherence of the Act with the area’s legal environment.
Keywords: Africa; Business and Management; Business ethics and social responsibility; Cooperatives; Economics; Economics of specific sectors; Employee-ownership and co-operatives; Finance; Law; Ownership and organization of enterprises; Social economy; Sociology of law; Welfare economics

UNCITRAL Expedited Arbitration Rules - UNCITRAL (United Nations, 2021)

Letztwillige Schiedsverfügungen : Geltungsgrund und Geltungsgrenzen - Gleim, Jakob (Studien zum ausländischen und internationalen Privatrecht, 2020)
Nach §1066 ZPO gelten die Vorschriften über vertraglich vereinbarte Schiedsgerichte entsprechend für "Schiedsgerichte, die in gesetzlich statthafter Weise durch letztwillige [...] Verfügungen angeordnet werden". Während solche letztwilligen Schiedsverfügungen im 20.Jahrhundert sehr selten waren, beschäftigen sie heute die deutschen Gerichte mit gewisser Regelmäßigkeit. Mit Zunahme der praktischen Relevanz rücken auch die dogmatischen Grundlagen letztwilliger Schiedsverfügungen in den Fokus: Warum darf der Erblasser nicht nur materielle, sondern auch prozessuale Verfügungen von Todes wegen treffen? Wie weit reicht die Zuständigkeit des letztwillig eingesetzten Schiedsgerichts? Und welches Recht ist anzuwenden, wenn der Erbfall grenzüberschreitende Bezüge aufweist? Jakob Gleim beantwortet diese Fragen und bezieht dabei im Rahmen eines Rechtsvergleichs auch das US-amerikanische Recht ein. Fürdie vorliegende Dissertation wurde Jakob Gleim mit der2020 der Max-Planck-Gesellschaft ausgezeichnet. Is it possible for the testator to mandate unilaterally that all disputes concerning the estate are to be arbitrated instead of litigated? While such a testamentary arbitration clause is an expression of the decedent’s freedom of disposition, it contradicts the beneficiaries’ right of access to a public court. In his dissertation, Jakob Gleim examines the tension between the decedent’s freedom of disposition and the rights of the beneficiaries, balancing these two positions against one another and thereby identifying the reasons and the limitations of the validity of testamentary arbitration clauses. While such clauses were rather rare in the 20th century, German courts have to deal with them more regularly nowadays. In his dissertation, Gleim explores the practical significance of testamentary arbitration clauses as well as their advantages and disadvantages. The author also addresses the questions of how far the jurisdiction of the arbitral tribunal extends and which law is to be applied in cross-border cases. The inquiry also includes insights gained from a comparative analysis of US-American law.
Keywords: Arbitaje; Arbitrage; Arbitragem; Arbitration; Arbitration clause; Bankruptcy; Clause d'arbitrage; Insolvency; Mediation; Negotiation

Guide de l'arbitrage de l'OMPI - Centre d’arbitrage et de médiation de l'OMPI (OMPI, 2020)

L'accord amiable - Mouralis, Denis; Ben Hamida, Walid (Droit des affaires, 2020)
Les « Modes Amiables de Résolution des Conflits » (MARC) représentent toutes les méthodes qui permettent de résoudre un différend sans recours au juge, telles que la médiation, la conciliation, la négociation, la négociation raisonnée, la transaction, la procédure participative, l’avis technique ou juridique amiable, procès simulé, etc. Aujourd’hui, dans la pratique des affaires, tant en France qu’à l’international, les MARC ont le vent en poupe. Issu d’un colloque, cet ouvrage s’adresse aux professionnels du droit, aux chercheurs, aux juristes d’entreprise et aux PME qui sont souvent tentés par le recours aux MARC et souhaitent connaître avec précision le régime et l’effet des accords amiables. L’objectif est d’explorer toutes les questions qui se posent lorsque les parties à un différend économique l'ont résolu au moyen d'un accord amiable, au moment où elles doivent concrètement mettre en œuvre cet accord. En particulier, comment rédiger l'accord et comment garantir son exécution ?
Keywords: Accord amiable; Accords de règlement internationaux; Droit européen; Droit international; Médiation

Criminalité maritime : Manuel à l'usage des praticiens de la justice pénale - Office des Nations Unies contre la drogue et le crime (Programme mondial de lutte contre la criminalité maritime, 2020)

The Use of Mediation in ISDS - UNCITRAL Working Group III Virtual Pre-Intersessional Meeting (Asian Academy of International Law Limited, 2020)
Keywords: ISDS; Investor-State Dispute Settlement; Mediation; Médiation